2017
DOI: 10.1016/j.indcrop.2017.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deficit irrigation on yield quantity and quality, water productivity and economic returns of four cultivars of hops in the Yakima Valley, Washington State

Abstract: Hop production, like all other water uses in the area, is facing water availability concerns. Deficit irrigation may address water scarcity issues in hop production. This study quantifies the effect of deficit irrigation on hop yield, quality, water productivity and grower profitability. Mt. Hood, Columbus, Chinook and Willamette cultivars were grown under three irrigation levels; 60, 80 and 100% of the crop's irrigation requirement, using a sub-surface drip irrigation system. Results show that hop plants gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
3
12
0
6
Order By: Relevance
“…An economic analysis was carried out to discern the effects of changes in the amounts of irrigation water applied and the resulting yields on the costs of production and the gross revenue according to the methodology reported by Nakawuka et al [33].…”
Section: Economic Analysismentioning
confidence: 99%
“…An economic analysis was carried out to discern the effects of changes in the amounts of irrigation water applied and the resulting yields on the costs of production and the gross revenue according to the methodology reported by Nakawuka et al [33].…”
Section: Economic Analysismentioning
confidence: 99%
“…A number of studies have correlated reduced cone yield with LW stress 8,10,11 . We found significantly decreased DW, A, g sw , E, C i , and ɸCO 2 under LW stress.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings relating to expression of genes in bitter acid pathways agree with previous studies that found reduced alpha acid content in hops exposed to HT stress [8][9][10] . Other studies that found no reductions in alpha acid content under LW stress 11 or cultivar-specific reactions to LW and HT stress 10 suggest cultivar differences in the temperature tolerance range of VPS and/or its regulatory mechanisms may be exploited to develop breeding lines with increased resilience to abiotic stress. Though plants grown in growth chambers under the conditions described here are very different than plants grown in the field, we anticipate that our findings will be helpful for breeding programs to identify traits and genomic regions for selection of new hop cultivars with more tolerance to abiotic stress such as HT and LW.…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, estudos demostram que o déficit hídrico não causa grande redução de beta ácidos (NAKAWUKA et al, 2017). Neve (1991), salienta que a temperatura não é o fator mais preponderante para altos rendimento em lúpulos.…”
Section: Condições Climáticas Para O Cultivo Do Lúpulounclassified